Toll-Like Receptor 2 Modulates Pulmonary Inflammation and TNF-α Release Mediated by Mycoplasma pneumoniae - Chen, Ming; Deng, Huan; Zhao, Yue; Miao, Xueqing; Gu, Haiyan; Bi, Ying; Zhu, Yifan; Guo, Yun; Shi, Shuang; Xu, Jiejing; Zhao, Deyu; Liu, Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives To investigate the roles that Toll-like receptors (TLRs) play in lung inflammation mediated by Mycoplasma pneumoniae (MP). Methods The changes in TLRs and tumor necrosis factor alpha (TNF-α) in peripheral blood of children with M. pneumoniae pneumonia (MPP) were monitored, and the interactions of signaling molecules regulating TNF-α release in A549 cells and neutrophils after M. pneumoniae stimulation were investigated. In TLR2 knockout (TLR2-/-) mice, the levels of TNF-α in bronchial alveolar lavage fluid (BALF) and peripheral blood after mycoplasma infection and the pathological changes in the lung tissue of mice were detected. Results TNF-α levels in peripheral blood of children with MPP were higher than those in non-infected children, and children with refractory MPP had the highest levels of TNF-α and TLR2. TNF-α secretion and TLR2, myeloid differentiation primary response 88 (MyD88) and phospho-p65(p-p65) levels were increased in stimulated cells. TNF-α secretion was suppressed upon siRNA-mediated TLR2 silencing. Pharmacological inhibition of nuclear factor-kappa B (NF-κB) and MyD88 effectively reduced TNF-α expression. Compared with wild-type mice, the TNF-α in serum and BALF decreased, and lung pro-inflammatory response was partially suppressed in TLR2-/- mice. Conclusion We concluded that TLR2 regulates M. pneumoniae-mediated lung inflammation and TNF-α release through the TLR2-MyD88-NF-κB signaling pathway.